Malaysia in the world economy, 1824-2011 capitalism, ethnic divisions, and "managed" democracy - Azlan Tajuddin 1961- (Lexington Books, 2012)
From colonialism to independent statehood, the extent of Malaysia's capitalist development has been significantly limited by its peripheral position in the world economy. As a result, the fruits of economic growth have not been equally shared among its citizens and neither has economic prosperity done much to foster greater multiculturalism or democracy in the country.